Charisma is ordinary: Weber, RiefF and the charismatic faith of biblical Israel - Legaspi, Michael C. (Journal of Jewish studies, 2019)
This article examines critical assessments of Max Weber's influential writings on Judaism. It focuses primarily on criticisms of Weber articulated by American Jewish sociologist Philip RiefF (1922--2006) and his one-time teacher Edward Shils (1910--1995). In a posthumously published 2007 work entitled Charisma: The Gift of Grace, and How It Has Been Taken Away from Us, RiefF takes aim at Weber's concept of charisma. In doing so, he argues for a novel yet traditional understanding of the contribution of Judaism to Western culture. This article explores challenges to Weber from RiefF and Shils under three headings: the distinctiveness of the Jewish people; the nature of charisma; and covenant and prophets. It reviews Weber's writings on these subjects and argues that RiefF correctly identifies ways in which Weber's concept of charisma remains beholden to Protestant thought and a mode of inquiry that obscures and opposes key aspects of Jewish self-understanding.